Management and eradication options for Queensland fruit fly. Issue 3 (17th August 2017) - Stringer, Lloyd D.; Kean, John M.; Beggs, Jacqueline R.; Suckling, D. Max
Abstract: Several tephritid fruit flies have explosive population growth and a wide host range, resulting in some of the largest impacts on horticultural crops, reducing marketable produce, and limiting market access. For these pests, early detection and eradication are routinely implemented in vulnerable areas. However, social and consumer concerns can limit the types of population management tools available for fruit fly incursion responses. Deterministic population models were used to compare eradication tools used at typical densities alone and in combination against the Queensland fruit fly ('Qfly'), Bactrocera tryoni . The models suggested that tools that prevent egg laying are likely to be most effective at reducing populations. Tools that induced mortality once Qfly was sexually mature only slowed population growth, as successful mating still occurred. Release of sterile Qfly when using the sterile insect technique (SIT) interferes with the successful mating of wild flies, and of the tools investigated here, SIT caused the greatest reduction in the population at the prescribed release rate. Used in tandem with SIT, protein baits slightly improved the rate of population reduction, but the male annihilation technique (MAT) almost nullified control by SIT due to the mortality induced on sterile flies. The model suggested that the most rapid decrease in population size would be achieved by SIT plus protein baits. However, the model predicted both the SIT and protein baits when used alone would result in population reduction. The MAT can be used prior to SIT release to increase overflooding ratios.